A survival guide to children's nursing - Edwards, Sharon , 1959-; Coyne, Imelda (Nurse's survival guide, 2013)
Starting a new placement? Moving to a new specialty? Revising? This series will give you the help you need with the procedures and problems faced by nurses today. This book includes sectoins on: Organising your job and yourself ; Working with patients ; Clinical information on a wide range of conditions ; Legal, health and safety issues and more. This book concentrates on the topic of children's nursing